Mycelial growth of two Lentinula edodes strains in culture media prepared with sawdust extracts from seven eucalyptus species and three eucalyptus clones - Andrade, Meire Cristina Nogueira de [UNESP]; Silva, Juliano Hojah Da [UNESP]; Minhoni, Marli Teixeira De Almeida [UNESP]; Zied, Diego Cunha [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2008)
The in vitro mycelial growth of Lentinula edodes strains LE-95/01 and LE-96/18 were evaluated in solid culture media prepared with sawdust extracts from seven eucalyptus species (E. saligna, E. grandis, E. urophylla, E. pellita, E. paniculata, E. citriodora, and E. camaldulensis) and three eucalyptus clones (E. grandis × E. urophylla hybrids). Evaluations were made every 48 hours by means of colony diameter measurements (mean of four transversely-oriented measurements), during ten days of incubation in the dark at 25ºC ±1°C. The experimental design consisted of randomized blocks, and treatment means were compared by Tukey test. The culture medium prepared from E. citriodora sawdust extract was the most promising to grow L. edodes strains LE-96/18 and LE-95/01. L. edodes strain LE-96/18 presented the fastest mycelial growth after incubation for ten days, regardless of sawdust extract type used in the culture medium.

Avaliou-se o crescimento micelial in vitro das linhagens LE-95/01 e LE-96/18 de Lentinula edodes, em meios de cultura sólidos à base de extrato de serragem de sete espécies (Eucalyptus saligna, E. grandis, E. urophylla, E. pellita, E. paniculata, E. citriodora e E. camaldulensis) e três clones (híbridos de E. grandis x E. urophylla) de eucalipto. As avaliações foram realizadas por meio de medições do diâmetro das colônias (média de quatro medidas diametralmente opostas), a cada 48 horas, durante dez dias de incubação, no escuro a 25ºC ±1°C. O delineamento experimental foi o de blocos casualizados, com uso do teste de Tukey para a comparação das médias. O meio de cultura à base de extrato de serragem de E. citriodora foi o mais promissor no crescimento das linhagens LE-96/18 e LE-95/01 de L. edodes. A linhagem LE-96/18 de L. edodes foi a que apresentou o crescimento micelial mais rápido após dez dias de incubação, independentemente do tipo de extrato de serragem utilizado no meio de cultura.
Crescimento micelial de duas linhagens de Lentinula edodes em meios de cultura à base de extrato de serragem de sete espécies e três clones de eucalipto
Keywords: shiitake; in vitro; cogumelo; shiitake; in vitro; mushroom